CRISPR–Cas9 screening reveals microproteins regulating adipocyte proliferation and lipid metabolism - Victor J. Pai; Huanqi Shan; Cynthia J. Donaldson; Joan M. Vaughan; Eduardo V. De Souza; Carolyn O’Connor; Michelle Liem; Antonio F. M. Pinto; Jolene Diedrich; Alan Saghatelian (Proceedings of the National Academy of Sciences, 2025)
Small open reading frames (smORFs) encode microproteins that play crucial roles in various biological processes, yet their functions in adipocyte biology remain largely unexplored. In a previous study, we identified thousands of smORFs in white and brown adipocytes derived from the stromal vascular fraction of mice using ribosome profiling. Here, we expand on this work by identifying additional smORFs related to adipocytes using the in vitro 3T3-L1 preadipocyte model. To systematically investigate the functional relevance of these smORFs, we designed a custom CRISPR/Cas9 single guide RNA (sgRNA) library and screened for smORFs influencing adipocyte proliferation and differentiation. Through a dropout screen and fluorescence-assisted cell sorting of lipid droplets, we identified dozens of smORFs that regulate either cell proliferation or lipid accumulation. The smORFs on the 5’- and 3’-untranslated regions (i.e., upstream smORFs (uORFs) and downstream smORFs (dORFs)) of functional genes can exert activity through cis-regulatory effects of the main ORF on these messenger RNAs (mRNAs), such as uORFs of MDM2 that impact proliferation. However, other smORFs, especially those from mRNAs with no other ORFs, point to a functional microprotein. Indeed, we tested a candidate smORF 1183 from a long noncoding RNA 923011K14Rik and demonstrated that the microprotein regulates adipocyte differentiation. These findings highlight the potential of CRISPR/Cas9-based screening to uncover functional smORFs and provide a framework for further exploration of microproteins in adipocyte biology and metabolic regulation.